Loss of TC-PTP in keratinocytes leads to increased UVB-induced autophagy - Obed Asare; Lindsey Shim; Cheol-Jung Lee; Jose Delgado; Natasha Quailes; Klarissa Zavala; Junsoo Park; Bilal Bin Hafeez; Yong-Yeon Cho; Subhash C. Chauhan; Dae Joon Kim (Cell Death Discovery, 2025)
Abstract Ultraviolet B (UVB) radiation can distort cellular homeostasis and predispose the skin to carcinogenesis. Amongst the deteriorating effects of the sun’s UVB radiation on cellular homeostasis is the formation of DNA photoproducts. These photoproducts can cause significant changes in the structure and conformation of DNA, inducing gene mutations which may accumulate to trigger the formation of skin cancer. Photoproducts are typically repaired by nucleotide excision repair. Notwithstanding, when the repair mechanism fails, apoptosis ensues to prevent the accumulation of mutations and to restore cellular homeostasis. This present study reports that T-cell protein tyrosine phosphatase (TC-PTP) can increase UVB-induced apoptosis by inhibiting autophagy-mediated cell survival of damaged keratinocytes. TC-PTP deficiency in 3PC mouse keratinocytes led to the formation of autophagic vacuoles and increased expression of LC3-II. We established human TC-PTP-deficient (TC-PTP/KO) HaCaT cells using the CRISPR/Cas9 system. TC-PTP/KO HaCaT cells exhibited increased cell survival upon UVB exposure, which was accompanied by increased expression of LC3-II and decreased expression of p62 compared to control cells. Pretreatment of TC-PTP/KO HaCaT cells with early-phase autophagy inhibitor, 3-methyladenine significantly decreased the expression of LC3-II and reduced cell survival in response to UVB irradiation in comparison with untreated TC-PTP/KO cells. Pretreatment of TC-PTP/KO HaCaT cells with late-phase inhibitor, chloroquine also significantly reduced cell viability with increased accumulation of LC3-II after UVB irradiation compared to untreated counterpart cells. While UVB significantly increased apoptosis in the engineered (Mock) cells, this was not observed in similarly treated TC-PTP/KO HaCaT cells. However, chloroquine treatment increased apoptosis in TC-PTP/KO HaCaT cells. Examination of human squamous cell carcinomas (SCCs) revealed that TC-PTP expression was inversely correlated with LC3 expression. Our findings suggest that TC-PTP negatively regulates autophagy-mediated survival of damaged cells following UVB exposure, which can contribute to remove damaged keratinocytes via apoptosis.